LINGUISTIC AND CULTURAL CODES OF THE MODERN UKRAINIAN LANGUAGE - Беркещук, Інна (SWorldJournal, 2026)
The article examines the concept of linguocultural code as a key tool for analyzing the interaction of language and culture. The main types of linguocultural codes of the modern Ukrainian language, their semantic, symbolic and axiological characteristics